When Social Networks Cross Boundaries: A Case Study of Workplace Use of Facebook and LinkedIn - Skeels, Meredith M.; Grudin, Jonathan (GROUP'09, Sanibel Island, Florida, USA, 2009)
The use of social networking software by professionals is increasing dramatically. How it is used, whether it enhances or reduces productivity, and how enterprise-friendly design and use might evolve are open questions. We examine attitudes and behaviors in a large, technologically-savvy organization through a broad survey and thirty focused interviews. We find extensive social and work uses, with complex patterns that differ with software system and networker age. Tensions arise when use spans social groups and the organization’s firewall. Although use is predominantly to support weak ties whose contribution to productivity can be difficult to prove, we anticipate rapid uptake of social networking technology by organizations.